NGƯNG TỤ 4-AMINO-3-(2-METOXY-4-PROPYLPHENOXYMETILEN)- (1H)-1,2,4-TRIAZOLE-5-THION VỚI CÁC HIĐROXY- VÀ METOXY- BENZALĐEHIT - Đĩnh, Nguyễn Hữu; Hiển, Nguyễn (Vietnam Journal of Chemistry, 2012)
A series of 8 imines were synthesized by condensing  4-amino-3-(2-methoxy-4-propylphenoxymethylen)-(1H)-1,2,4-triazole-5-thione with hydroxy- and methoxy   benzaldehydes. The structure of the imines were confirmed by UV, EI MS, IR and 1H NMR spectroscopy, in some cases,  2D NMR spectra are also used